2007
DOI: 10.1074/jbc.m610090200
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Function Relationships of the Viral RNA-dependent RNA Polymerase

Abstract: Studies of the RNA-dependent RNA polymerase (RdRp) from poliovirus (PV), 3Dpol, have shown that Asn-297 permits this enzyme to distinguish ribose from 2 -deoxyribose. All animal RNA viruses have Asn at the structurally homologous position of their polymerases, suggesting a conserved function for this residue. However, all prokaryotic RNA viruses have Glu at this position. In the presence of Mg 2؉ , the apparent affinity of Glu-297 3Dpol for 2 -deoxyribonucleotides was decreased by 6-fold relative to wild type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(25 citation statements)
references
References 53 publications
1
24
0
Order By: Relevance
“…Importantly, this model explains and predicts biological phenotypes (2,4,5,20). However, VPg uridylylation occurs 10 -50-fold slower in vitro than necessary to support the rate constant (ϳ0.1/s) for initiation calculated from biological data (see Ref.…”
mentioning
confidence: 68%
See 3 more Smart Citations
“…Importantly, this model explains and predicts biological phenotypes (2,4,5,20). However, VPg uridylylation occurs 10 -50-fold slower in vitro than necessary to support the rate constant (ϳ0.1/s) for initiation calculated from biological data (see Ref.…”
mentioning
confidence: 68%
“…Processive uridylylation is likely essential as VPg-pU does not chase into VPg-pUpU in vitro (20). In addition, a highly active 3Dpol derivative that produces much more 4 I. G. Goodfellow, unpublished results.…”
Section: Uridylylation Of Vpg Precursor Proteins-two Observationsmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, it is striking that these two substitutions, located in different domains of the Q␤ replicase and outside the catalytic site, gave rise to such similar phenotypes with respect to AZC tolerance, revealing a redundancy that has not been observed in other viral systems. Previous work has demonstrated that the fidelity of RNA virus replicases can be modulated by protein domains located outside the catalytic site (66)(67)(68). For instance, a conformational change consisting of the reorientation of the triphosphate moiety of the incoming nucleotide is a key fidelity checkpoint for the poliovirus replicase (68).…”
Section: Discussionmentioning
confidence: 99%